The impact of banking sector reform in a transition economy: Evidence from Kyrgyzstan - Brown, Martin; Maurer, Maria Rueda; Pak, Tamara; Tynaev, Nurlanbek (Journal of Banking & Finance, 2009)
We examine the impact of financial sector reform on interest rate levels and spreads using Kyrgyz bank-level data from 1998 to 2005. We find that, in addition to macroeconomic stabilization, structural reforms to the banking sector significantly contributed to lower interest rates. In particular, our results suggest that foreign bank entry and regulatory efforts to increase average bank size were important in reducing deposit rates. In contrast, we find little evidence that banking sector reform or macroeconomic stabilization has impacted interest rate spreads.